2006
DOI: 10.1038/sj.onc.1210101
|View full text |Cite
|
Sign up to set email alerts
|

eEF1A2 activates Akt and stimulates Akt-dependent actin remodeling, invasion and migration

Abstract: eEF1A2 (eukaryotic protein elongation factor 1 alpha 2) is a protein translation factor that is likely a human oncogene by virtue of its capacity to transform mammalian cells and its high expression in tumors of the ovary, breast and lung. Here, we show that expression of eEF1A2 is sufficient to stimulate the formation of filopodia in BT549 human breast cancer cells and non-transformed Rat2 cells. Filopodia formation in eEF1A2-expressing cells is dependent on the activity of phosphatidylinositol-3 kinase (PI3K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(133 citation statements)
references
References 50 publications
(71 reference statements)
8
123
0
1
Order By: Relevance
“…This effect was also associated with an inhibition of apoptosis of approximately 70% as evaluated by cytofluorimetric analysis (Becton Dickinson; Palo Alto, CA, USA) with propidium iodide (Sigma, St. Louis, MO, USA), thus confirming the oncogenic properties of eEF1A2. Similar behavior exerted by eEF1A2 was also described in BT549 human breast cancer cells (84) . In fact, filopodia formation in eEF1A2-expressing cells was dependent on the activity of PI3K, ROCK and Akt kinases.…”
Section: Eef1a Substratesupporting
confidence: 52%
“…This effect was also associated with an inhibition of apoptosis of approximately 70% as evaluated by cytofluorimetric analysis (Becton Dickinson; Palo Alto, CA, USA) with propidium iodide (Sigma, St. Louis, MO, USA), thus confirming the oncogenic properties of eEF1A2. Similar behavior exerted by eEF1A2 was also described in BT549 human breast cancer cells (84) . In fact, filopodia formation in eEF1A2-expressing cells was dependent on the activity of PI3K, ROCK and Akt kinases.…”
Section: Eef1a Substratesupporting
confidence: 52%
“…In plants, EF1A1 acts as an activator of phosphatidylinositol 4-kinase (PI4K) and regulates phosphatidylinositol (4,5)-bisphosphate via its interaction with phospholipase CÎł1 (Yang et al, 1993;Yang and Boss, 1994). Recently, EF1A1 was identified as a binding partner of Akt2 (Lau et al, 2006), whereas the other isoform EF1A2 was shown to bind and activate PI4K and Akt, depending on the intracellular abundance of phosphatidylinositol (3,4,5)-trisphosphate (Amiri et al, 2006;Jeganathan and Lee, 2007). In this regard, DLC1 is also a target for Akt kinase signaling in response to insulin (Hers et al, 2006).…”
Section: Journal Of Cell Science 122 (3)mentioning
confidence: 99%
“…Moreover, downregulation of eEF1A2 expression leads to decreased expression of pAkt1 and to less extent of pAkt2 and promotes apoptosis [85]. Thus, eEF1A2 interaction with pAkt represents an important mechanism for the regulation of Akt-dependent survival signalling pathways in cancer [85,86].…”
Section: Anti-apoptotic Activity In Cancer Cells Role Of Translationmentioning
confidence: 99%
“…In mouse fibroblast cell line NIH3T3, eEF1A2 interacts with peroxiredoxin-I (Prdx-I), resulting in increased activation of Akt, reduced activation of caspases 3 and 8, and protection against apoptotic death [84]. Moreover, downregulation of eEF1A2 expression leads to decreased expression of pAkt1 and to less extent of pAkt2 and promotes apoptosis [85]. Thus, eEF1A2 interaction with pAkt represents an important mechanism for the regulation of Akt-dependent survival signalling pathways in cancer [85,86].…”
Section: Anti-apoptotic Activity In Cancer Cells Role Of Translationmentioning
confidence: 99%